Effect of cyclosporine A on the hearing loss in Behçet's disease - Elidan, J; Levi, H; Cohen, E; BenEzra, D (Annals of otology, rhinology & laryngology, 1991)
Thirty-five patients with Behçet's disease (20 under cyclosporine A [CyA] treatment and 15 under the conventional therapy), 12 patients suffering from endogenous uveitis, and 35 normal subjects were evaluated audiologically before entering the study and were followed up for at least a year. Twenty-eight Behçet patients (80%) showed some degree of hearing loss. The averaged pure tone audiogram of the Behçet group showed statistically significant auditory deficits in comparison with that of the control group. None of either the Behçet group or the uveitis group showed any hearing deterioration during the follow-up period. Five Behçet patients under CyA therapy demonstrated improvement in their hearing. The difference between the two groups of Behçet patients (CyA versus conventional treatment) was found to be statistically significant (p less than .05). Thus, CyA might serve as an important mode of treatment of sensorineural hearing loss on an inflammatory "autoimmune" background.